One Health for neglected tropical diseases. (9th November 2020) - Laing, Gabrielle; Vigilato, Marco Antonio Natal; Cleaveland, Sarah; Thumbi, S M; Blumberg, Lucille; Salahuddin, Naseem; Abdela-Ridder, Bernadette; Harrison, Wendy
Abstract: The forthcoming World Health Organization road map for neglected tropical diseases (NTDs) 2021–2030 recognises the complexity surrounding control and elimination of these 20 diseases of poverty. It emphasises the need for a paradigm shift from disease-specific interventions to holistic cross-cutting approaches coordinating with adjacent disciplines. The One Health approach exemplifies this shift, extending beyond a conventional model of zoonotic disease control to consider the interactions of human and animal health systems within their shared environment and the wider social and economic context. This approach can also promote sustainability and resilience within these systems. To achieve the global ambition on NTD elimination and control, political will, along with contextualised innovative scientific strategies, is required.